Analysis of the effect of Boezem development as flood control - Aridhadinata, Pramudya; Laksono, Agung Dwi; Novita, Widia Ade; Cahyadi, Achmad Faishal Nur; Sari, Galuh Ismaya (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2024)
Background: Flooding is a frequent problem in Dukuh Kupang, Surabaya, causing material losses and disrupting daily activities. The construction of boezems, which are retention ponds to temporarily store rainwater, is considered a potential solution to control flooding in this area. This study aims to analyze the effect of boezem construction on flood control in Dukuh Kupang with the hope of providing new insights into the effectiveness of boezem as flood control infrastructure and providing recommendations for improved flood management strategies in the future. Methods: This study used a descriptive method. Data were collected through questionnaires and scored using a Likert scale.  Finding: The results revealed that the feasibility score of boezem construction was 60.2%, indicating that boezem construction is considered quite feasible as a flood control solution, but there is still room for improvement. Conclusion: Respondents in this study recognized the benefits of boezem construction, but also expressed concerns or factors that are not yet fully supportive. There is a negative stigma among the community regarding the construction of boezems, which is largely due to the lack of socialization and community participation in the development process. Novelty/Originality of this study: A study on the effectiveness of booze in Surabaya evaluates technical aspects and considers community perceptions, providing a holistic approach to assessing flood control infrastructure.